(untitled) (The International Journal for Scientific Research, 2024)
This study aimed to identify the role of digital media in disseminating information about behavioral deviation in the kingdom of Bahrain and discuss the level of awareness of the risks of behavioral deviation and determine the existence of differences in the opinions of the sample members about the role of digital media in promoting awareness of the risks of behavioral deviation among young people in the kingdom of Bahrain and attributed to variables (gender - age - educational level). Where the descriptive analytical approach was used, and we were selected for a sample represented in all university students in the kingdom of Bahrain, which is the available sample of those who use digital media tools consisting of (100) single university students in the kingdom of Bahrain, who were selected in the available way, including (47) males and (53) females by choosing (the questionnaire method) in the analysis of the study. The study found that digital media has a significant impact on the behaviors of university youth, and that young people are able to express their awareness of the importance of digital media and its roles in contemporary societies, and university students express a high level of trust in digital media. The study recommended those concerned to produce digital content that promotes positive moral and social values, such as educational videos, blogs and awareness articles that explain the dangers of behavioral deviation and its impact on the individual and society.